Bdellovibrio bacteriovorus directly attacks Pseudomonas aeruginosa and Staphylococcus aureus Cystic fibrosis isolates - Iebba, Valerio; Totino, Valentina; Santangelo, Floriana; Gagliardi, Antonella; Ciotoli, Luana; Virga, Alessandra; Ambrosi, Cecilia; Pompili, Monica; De Biase, Riccardo V.; Selan, Laura; Artini, Marco; Pantanella, Fabrizio; et al. (Frontiers in Microbiology, 2014)
Bdellovibrio bacteriovorus is a predator bacterial species found in the environment and within the human gut, able to attack Gram-negative prey. Cystic fibrosis (CF) is a genetic disease which usually presents lung colonization by Pseudomonas aeruginosa or Staphylococcus aureus biofilms. Here, we investigated the predatory behaviour of B. bacteriovorus against these two pathogenic species with: i) broth culture; ii) ‘static’ biofilms; iii) field emission scanning electron microscope (FESEM); iv) ‘flow’ biofilms; v) zymographic technique. We had the first evidence of B. bacteriovorus survival with a Gram-positive prey, revealing a direct cell-to-cell contact with S. aureus and a new ‘epibiotic’ foraging strategy imaged with FESEM. Mean attaching time of HD100 to S. aureus cells was 185s, while ‘static’ and ‘flow’ S. aureus biofilms were reduced by 74% (at 24h) and 46% (at 20h), respectively. Furthermore, zymograms showed a differential bacteriolytic activity exerted by the B. bacteriovorus lysates on P. aeruginosa and S. aureus. The dual foraging system against Gram-negative (periplasmic) and Gram-positive (epibiotic) prey could suggest the use of B. bacteriovorus as a ‘living antibiotic’ in CF, even if further studies are required to simulate its in vivo predatory behaviour.